1979
DOI: 10.1111/j.1469-8137.1979.tb02297.x
|View full text |Cite
|
Sign up to set email alerts
|

SENSITIVITY OF ROOTING AND TOLERANCE TO COPPER IN AGROSTIS TENUIS SIBTH.

Abstract: Summary The rooting response of seven populations of Agrostis tenuis Sibth. to a range of copper concentrations in calcium nitrate solution is described. Variation in both index of tolerance and sensitivity of rooting to increased copper levels were found and shown to be phenotypically independent characters. It is suggested that rooting sensitivity to a range of copper concentrations provides a further measure of copper tolerance which is independent of the methods previously employed for assessing tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…1). It is important that, for single-concentration tolerance tests, a wide range of concentrations be tried initially, to find a concentration which effectively separates tolerant from nontolerant plants; however, for a complete understanding of the nature of variation in tolerance and its possible ecological implications, a multiple-concentration approach is preferable (Wilkins, 1978;Nicholls and McNeilly, 1979). The traditional method of quantifying tolerance as the ratio of root growth in metal solution to control growth in uncontaminated conditions (Wilkins, 1957;Jowett, 195 8) has the disadvantage of being statistically unwieldy in parallel-control experiments (Wilkins, 1978) where each plant is tested in only one concentration rather than sequentially in two or more concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…1). It is important that, for single-concentration tolerance tests, a wide range of concentrations be tried initially, to find a concentration which effectively separates tolerant from nontolerant plants; however, for a complete understanding of the nature of variation in tolerance and its possible ecological implications, a multiple-concentration approach is preferable (Wilkins, 1978;Nicholls and McNeilly, 1979). The traditional method of quantifying tolerance as the ratio of root growth in metal solution to control growth in uncontaminated conditions (Wilkins, 1957;Jowett, 195 8) has the disadvantage of being statistically unwieldy in parallel-control experiments (Wilkins, 1978) where each plant is tested in only one concentration rather than sequentially in two or more concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic plasticity represents a fundamental strategy for perennial plants to survive environmental change and respond to favourable conditions. For several species it has been found that variation in response to environmental change may reflect differences in the genetic control of phenotypic plasticity (Bradshaw 1965 ;Khan, Antonovicw & Bradshaw, 1976;Jain, 1978;Nicholls & McNeilly, 1979;Marshall, Levin & Fowler, 1986;Shaw, 1986;Shaw & Antonovics, 1986). Such variation in plasticity may be related to the habitat from which particular plants are collected, as reported for Plantago major (Lotz & Blom, 1986), Ammophila arenaria (Gray, 1985), and Collomia linearis (Wilken, 1977).…”
Section: Between Population Variation In Plasticitymentioning
confidence: 91%
“…An alternative assessment of tolerance has been proposed by Nicholls & McNeilly (1979) based upon the correlation between root length and a range of metal concentrations, following a similar approach to problems of genotype x environment interaction by Finlay & Wilkinson (1963). The data for the correlations between logj^ root length and concentrations of the five metals used in the present experiment (Table 2) would seem to provide more critical estimates of tolerance to those metals than tolerance indices, since the bias of control root lengths is minimised, and patterns of overall response to heavy metals are not adequately reflected in their response to a single test level of a metal.…”
Section: Discussionmentioning
confidence: 99%